Early COVID-19 lockdown in Greece and idiopathic pulmonary fibrosis: a beneficial "impact" beyond any expectation. Issue 3 (25th March 2021) - Papiris, Spyros A.; Bouros, Demosthenes; Markopoulou, Katerina; Kolilekas, Lykourgos; Papaioannou, Andriana I.; Tzilas, Vasilios; Tzouvelekis, Argyrios; Fouka, Eva; Papakosta, Despoina; Daniil, Zoe; Steiropoulos, Paschalis; Gogali, Athina; et al.
Idiopathic pulmonary fibrosis (IPF) is an irreversibly progressive diffuse lung disease characterised by a usual interstitial pneumonia (UIP) pattern. IPF presents with an ominous prognosis with a median survival of around 5 years [1]. The development of an acute exacerbation, histologically diffuse alveolar damage (DAD) upon UIP, represents the most devastating of its complications and leads to death in the majority of patients admitted to the intensive care unit (ICU) [2–4]. Viral infections in the setting of an altered host lung microbiome are likely important triggers of acute exacerbations of IPF and subsequent acute respiratory distress syndrome (ARDS) [4, 5]. During the lockdown, IPF patients experienced lower than expected COVID-19, suggesting that simple measures for the winter months, such as face masking, clean hands, physical distancing could be adopted as promising advances in non-pharmacological therapy https://bit.ly/2ISi2EV